Insight into the Recent Advancement of 1,3,4 Oxadiazoles as Potential EGFR and Telomerase Inhibitory for Anticancer Activity - Jain, Ayush; Majee, Chandana; Mazumder, Rupa; Mazumder, Avijit (Indian Journal of Pharmaceutical Education and Research, 2026)
Cancer is acknowledged as one of most perilous diseases, with significant challenges associated with existing anticancer therapies, including issues of drug resistance, narrow therapeutic windows, and the manifestation of severe and diverse adverse effects. Given the current state of oncology research, there is an urgent need to drive the development of innovative anticancer therapeutics that target unique molecular pathways to enhance the effective management of cancer. In this context, targeting the Epidermal Growth Factor Receptor (EGFR) and telomerase inhibition emerges as a promising strategy, with ongoing investigation focusing on 1,3,4-oxadiazole derivatives for this purpose. The findings of diverse researchers investigating these molecular frameworks have been systematically reviewed and analysed, culminating in a comprehensive summary. This review is centered on elucidating the Structure-Activity Relationships (SARs) and computational analyses of a range of 1,3,4-oxadiazole derivatives, specifically focusing on documented cytotoxicity, EGFR-TK inhibitory potential, and their efficacy as telomerase inhibitors in the context of anticancer activity. 1,3,4-Oxadiazole hybrids/derivatives with diverse substitutions exhibit efficacy as pharmacophores in achieving robust anticancer effects. Following a comprehensive literature survey, it is concluded that this review will undoubtedly furnish researchers with substantial insights to facilitate the design and synthesis of potent hybrids/derivatives capable of inhibiting EGFR and telomerase, thereby enhancing their therapeutic potential against cancer.
Keywords: 1; 3; 4-oxadiazole; Anticancer Activity; Cancer; EGFR-TK Inhibitors; Hybrids; Telomerase; Inhibition; Telomerase